The Cubango-Okavango River Basin Multi-Sector Investment Opportunities Analysis : Summary Report - World Bank (World Bank, Washington, DC, 2019)
The Cubango-Okavango River Basin is one of the world's most unique, near pristine free-flowing rivers, and central to sustainable economic development within the arid landscapes of southern Africa. The complex flood pulse cycle provides important services for local communities while supporting a rich and unique biodiversity that makes it a wetland of international importance and World Heritage site. However, the commitments to peace and prosperity among the three countries—Angola, Botswana, and Namibia—and the broader efforts of the Southern African Development Community to facilitate greater regional integration provide prospects for increased and improved development. The Multi-Sector Investment Opportunities Analysis is part of a systematic strategy by the Permanent Okavango River Basin Water Commission, a body established in 1994 by Angola, Botswana, and Namibia, to promote coordinated and sustainable water resources management, while addressing the legitimate social and economic needs of the member states. The environmental integrity and long-term protection of the basin depends on addressing the underlying drivers of poverty. Accelerated environmental changes in the basin are largely driven by four factors—population dynamics, land use change, poverty, and climate change—leading to deterioration in water quality, changes in the flood pulse and diminishing biota. As a result, the risks associated with persistent poverty threaten the long-term sustainability of the basin.